In Situ Investigation of Reversible Exsolution/Dissolution of CoFe Alloy Nanoparticles in a Co‐Doped Sr2Fe1.5Mo0.5O6−δ Cathode for CO2 Electrolysis. Issue 6 (1st January 2020) - Lv, Houfu; Lin, Le; Zhang, Xiaomin; Song, Yuefeng; Matsumoto, Hiroaki; Zeng, Chaobin; Ta, Na; Liu, Wei; Gao, Dunfeng; Wang, Guoxiong; Bao, Xinhe
Abstract: Reversible exsolution and dissolution of metal nanoparticles in perovskite has been investigated as an efficient strategy to improve CO2 electrolysis performance. However, fundamental understanding with regard to the reversible exsolution and dissolution of metal nanoparticles in perovskite is still scarce. Herein, in situ exsolution and dissolution of CoFe alloy nanoparticles in Co‐doped Sr2 Fe1.5 Mo0.5 O6–δ (SFMC) revealed by in situ X‐ray diffraction, scanning transmission electron microscopy, environmental scanning electron microscopy, and density functional theory calculations are reported. Under a reducing atmosphere, facile exsolution of Co promotes reduction of the Fe cation to generate CoFe alloy nanoparticles in SFMC, accompanied by structure transformation from double perovskite to layered perovskite at 800 °C. Under an oxidizing atmosphere, spherical CoFe alloy nanoparticles are first oxidized to flat CoFeO x nanosheets, and then dissolved into the bulk with structure evolution from layered perovskite back to double perovskite. Electrochemically, CO2 electrolysis performance can be retrieved during 12 redox cycles due to the regenerative ability of the CoFe alloy nanoparticles. The anchoring of the CoFe alloy nanoparticles in SFMC perovskite via reduction shows enhanced CO2 electrolysis performance and stability compared with the parent SFMC perovskite. Abstract : Reversible exsolution and dissolution of CoFe alloy nanoparticles in Sr2.0 Fe1.35 Co0.2 Mo0.45 O6− δ double perovskite are investigated using in situ X‐ray diffraction, scanning transmission electron microscopy, and environmental scanning electron microscopy in combination with density functional theory calculations.